AN INVESTIGATION OF PRONUNCIATION DIFFICULTIES AMONG FIRST-YEAR STUDENTS IN ENGLISH EDUCATION STUDY PROGRAM - Gusfin Maulidyawanti Moonti; Monalysa Laonga (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT Pronunciation plays a central role in the professional preparation of English teachers, as pre-service teachers are expected not only to communicate intelligibly but also to model accurate spoken English for their future students. This study investigated the pronunciation difficulties experienced by first-year students in an English Education Study Program, focusing on segmental and suprasegmental error patterns, pronunciation-related anxiety, and the factors underlying these difficulties. Employing a descriptive mixed-methods design with a concurrent triangulation strategy, data were collected from ten first-year students through a pronunciation test, a closed-ended questionnaire, and semi-structured interviews. The findings reveal that pronunciation difficulties were multidimensional rather than confined to articulation alone. Consonant errors (37.6%) and vowel errors (30.3%) were the most frequent, particularly involving dental fricatives (/θ/, /ð/) and the /ɪ/–/iː/ vowel contrast, patterns consistent with the revised Speech Learning Model (SLM-r) and the Perceptual Assimilation Model (PAM). Word stress and sentence intonation errors, though less frequent, were compounded by participants' limited awareness of these features, reflecting insufficient prior instructional attention to suprasegmental aspects of pronunciation. In addition, pronunciation-related anxiety emerged as a significant factor, with participants reporting nervousness and avoidance behavior during oral communication. These results indicate that pronunciation competence among pre-service English teachers develops through the interaction of first-language phonological transfer, instructional experience, and affective readiness. The study recommends that pronunciation instruction in English teacher education programs explicitly address both segmental and suprasegmental features while fostering supportive, low-anxiety speaking environments to strengthen learners' intelligibility and communicative confidence. ABSTRAK Pengucapan memegang peranan penting dalam penyiapan profesional calon guru bahasa Inggris, karena mahasiswa calon guru dituntut tidak hanya mampu berkomunikasi secara jelas, tetapi juga menjadi model pengucapan yang benar bagi peserta didiknya kelak. Penelitian ini bertujuan untuk mengkaji kesulitan pengucapan yang dialami oleh mahasiswa tahun pertama Program Studi Pendidikan Bahasa Inggris, dengan berfokus pada pola kesalahan segmental dan suprasegmental, kecemasan terkait pengucapan, serta faktor-faktor yang melatarbelakangi kesulitan tersebut. Dengan menggunakan desain deskriptif metode campuran (mixed-methods) melalui strategi triangulasi konkuren, data dikumpulkan dari sepuluh mahasiswa tahun pertama melalui tes pengucapan, angket tertutup, dan wawancara semi-terstruktur. Hasil penelitian menunjukkan bahwa kesulitan pengucapan bersifat multidimensional dan tidak hanya terbatas pada masalah artikulasi. Kesalahan konsonan (37,6%) dan vokal (30,3%) merupakan jenis kesalahan yang paling sering ditemukan, terutama pada bunyi frikatif dental (/θ/, /ð/) dan kontras vokal /ɪ/–/iː/, pola yang sejalan dengan revised Speech Learning Model (SLM-r) dan Perceptual Assimilation Model (PAM). Kesalahan tekanan kata dan intonasi kalimat, meskipun lebih jarang muncul, diperparah oleh rendahnya kesadaran partisipan terhadap aspek-aspek tersebut, yang mencerminkan kurangnya perhatian pembelajaran terhadap unsur suprasegmental sebelumnya. Selain itu, kecemasan terkait pengucapan juga muncul sebagai faktor yang signifikan, ditandai dengan rasa gugup dan perilaku menghindar saat berkomunikasi lisan. Temuan ini menunjukkan bahwa kompetensi pengucapan calon guru bahasa Inggris berkembang melalui interaksi antara transfer fonologis bahasa pertama, pengalaman pembelajaran, dan kesiapan afektif. Penelitian ini merekomendasikan agar pembelajaran pengucapan dalam program pendidikan guru bahasa Inggris secara eksplisit membahas unsur segmental maupun suprasegmental, serta menciptakan lingkungan berbicara yang suportif dan rendah kecemasan guna memperkuat kejelasan ucapan dan kepercayaan diri komunikatif mahasiswa.